1997
DOI: 10.1073/pnas.94.26.14389
|View full text |Cite
|
Sign up to set email alerts
|

RGS2/G0S8 is a selective inhibitor of Gqα function

Abstract: RGS (regulators of G protein signaling) proteins are GTPase activating proteins that inhibit signaling by heterotrimeric G proteins. All RGS proteins studied to date act on members of the Gi␣ family, but not Gs␣ or G12␣. RGS4 regulates Gi␣ family members and Gq␣. RGS2 (G0S8) is exceptional because the G proteins it regulates have not been identified. We report that RGS2 is a selective and potent inhibitor of Gq␣ function. RGS2 selectively binds Gq␣, but not other G␣ proteins (Gi, Go, Gs, G12͞13) in brain membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
304
3
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(329 citation statements)
references
References 26 publications
17
304
3
5
Order By: Relevance
“…RGS2 mainly attenuates Gaqmediated GPCR signaling (Heximer et al, 1997;Heximer, 2004). It is noteworthy that 5-HT2AR is also coupled with Gaq (Adlersberg et al, 2000), and its levels have been shown to be significantly higher in the prefrontal cortex (BA 8 and/ or 9) of the postmortem brains of suicide victims Mann et al, 1986;Arora and Meltzer, 1989;Arango et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…RGS2 mainly attenuates Gaqmediated GPCR signaling (Heximer et al, 1997;Heximer, 2004). It is noteworthy that 5-HT2AR is also coupled with Gaq (Adlersberg et al, 2000), and its levels have been shown to be significantly higher in the prefrontal cortex (BA 8 and/ or 9) of the postmortem brains of suicide victims Mann et al, 1986;Arora and Meltzer, 1989;Arango et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…For these studies we took advantage of two well-characterized specific inhibitors of Gaq and Gbg G protein subunits: the regulator of G protein signaling-2 (RGS2) and CD8-bARK, respectively. RGS2 is a GTPase activating protein that is a selective and potent inhibitor of Gaq but not other Ga G protein subunits [Heximer et al, 1997], while CD8-bARK is a chimeric molecule comprised of the Gbg-binding domain of the b-adrenergic receptor kinase fused to the extracellular and transmembrane domains of the CD8 molecule, and works by scavenging free Gbg subunits and preventing them from interacting with their downstream effectors [Crespo et al, 1995]. When expressed in 3T3-L1 preadipocytes by retroviral-mediated gene transfer, we found that expression of RGS2, but not CD8-bARK, was able to significantly attenuate the inhibitory effects of PGF2a on adipocyte differentiation, thereby indicating that PGF2a inhibits adipocyte differentiation via a signaling pathway that is dependent upon the specific activation of Gaq, but not Gbg, G protein subunits.…”
Section: Pgf2a Inhibits Adipogenesis Through a Gaq-calcium-dependent mentioning
confidence: 99%
“…BM1 appeared to be RGS2/G0S8 (GenBank accession number L13391), a regulatory protein involved in cellular signal transduction early in the cell cycle. 47,48 BM4 turned out to represent proprotein convertase 2 (GenBank accession number NM_002594), 49,50 an intracellular serine proteinase involved in the processing of autocrine factors that may induce tumor growth and angiogenesis. [51][52][53] Expression of the RGS2/G0S8 protein is earlier demonstrated in blood mononuclear cells exclusively.…”
Section: Differential Display Analysis Of Immunoselected Breast Carcimentioning
confidence: 99%